Types of financial aid delivered during COVID-19 pandemic: a systematic literature review/ Abd Hadi Mustaffa and Noryati Ahmad - Mustaffa, Abd Hadi; Ahmad, Noryati (Universiti Teknologi MARA Selangor, 2022)
COVID-19 pandemic has become worsen day by day. Almost 200 countries' economies were affected, and it shows that global GDP declined by 6.7% in the year 2020. In detail, the community and businesses were affected by losing jobs and lost revenue. Hence, most countries face challenges by forcing them to deliver and channel financial aids to recover and stabilize their economy. The study's main objective is to systematically review the financial aids of countries during the COVID-19 pandemic in a global context. The review was guided by Preferred Reporting Items for Systematic Reviews and MetaAnalysis (PRISMA). As a result, 20 articles were selected and systematically reviewed. The results via thematic analysis identified six themes, 1) government economic booster, 2) employee stimulus package, 3) financial assistance to business, 4) community financial assistance, 5) tax or debt relief, and 6) health and emergency aid. The six themes were further discussed regarding how financial aids works, which party is handling more financial aids, a few related issues, and recommendations to improve financial aid in the future crisis. In addition, this study provides two significant contributions in the later section.